2014
DOI: 10.1080/15421406.2014.935978
|View full text |Cite
|
Sign up to set email alerts
|

Study on n-type Doped Electron-Transporting Layers in OLEDs by Electron Spin Resonance

Abstract: We present an electron spin resonance (ESR) study of Cs 2 CO 3 and LiF doped tris(8-hydroxyquinoline) aluminum (Alq 3 ) thin films. The g values of the Cs 2 CO 3 and LiF doped Alq 3 thin films were obtained as 2.0040 and 2.0028, repectively. The g value of the LiF doped film was very close to a theoretically calculated one for an isolated Alq 3 radical anion, while Cs 2 CO 3 doped film showed a large g shift. This feature can be explained by large spin-orbit interaction caused by heavy Cs atoms. While doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Here, the g factor was evaluated from the resonance magnetic field where the ESR spectrum with a first derivative form has a value of zero, and the Δ H pp value was evaluated as the difference between the two magnetic fields at a peak and a valley in the ESR spectrum. The g factor obtained by the fitting analysis is consistent with that of the Alq 3 radial anions ( g = 2.0028) obtained from the previous ESR study for Li‐doped Alq 3 films and that obtained from the DFT calculation . From this consistency, the origin of the signal A is ascribed to the Alq 3 radical anions formed by electron doping due to the reaction at the interfaces of Alq 3 /LiF/Al layer: 3LiF + Al + 3Alq 3 → AlF 3 + 3Li + Alq 3 − …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Here, the g factor was evaluated from the resonance magnetic field where the ESR spectrum with a first derivative form has a value of zero, and the Δ H pp value was evaluated as the difference between the two magnetic fields at a peak and a valley in the ESR spectrum. The g factor obtained by the fitting analysis is consistent with that of the Alq 3 radial anions ( g = 2.0028) obtained from the previous ESR study for Li‐doped Alq 3 films and that obtained from the DFT calculation . From this consistency, the origin of the signal A is ascribed to the Alq 3 radical anions formed by electron doping due to the reaction at the interfaces of Alq 3 /LiF/Al layer: 3LiF + Al + 3Alq 3 → AlF 3 + 3Li + Alq 3 − …”
Section: Resultssupporting
confidence: 87%
“…For investigating organic devices such as the OLEDs and the constitution materials at a molecular level, electron spin resonance (ESR) spectroscopy is one of most suitable techniques because the ESR method is a highly sensitive and nondestructive technique for directly observing radicals and charges with spins in organic semiconductors and their devices at a molecular level . The ESR studies have demonstrated a clear correlation between the performance deterioration and the charge (and spin) accumulation (or deep trappings) in photovoltaic devices, and have clarified the degradation mechanism due to the charge (and spin) formation during device fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…47 In addition, the g value increases owing to the large spin−orbit interactions because of bromine heavy atoms. 48 To examine the effects of residual bromines at PTB7 chain ends, we performed DFT calculation using Gaussian 09. 49 As a model molecule of PTB7, we utilized oligomers shown in Figure 2a,b.…”
Section: Resultsmentioning
confidence: 99%
“…For Alq 3 , the calculated value ( g ave = 2.00285) is considerably smaller than the experimental value ( g = 2.0036 ± 0.0001). The reason for the larger experimental value may be due to an effect of spin–orbital interaction in a positive EMIM ion in the ion-gel and the Alq 3 anion 42 . That is, an electron on Alq 3 spreads over the positively charged EMIM, which may increase the g -factor by the enhanced spin–orbital interaction.…”
Section: Resultsmentioning
confidence: 98%